A representação da subjetividade do indivíduo usuário de drogas na linguagem jornalística - Barbosa, Jacquelline Rodrigues (2017)
Envisioning to study the mediatic discourse related to the individual / drug user, the role of the media in disseminating the discursive practices attributed to this public was investigated. In order to achieve this, the first step was to comprehend the historical process of drugs in humanity, its mechanism of criminalization and the journalistic language referring to drug addiction. It is understood that there is a discourse involving the "drug war", disseminated by the state and by the cultural industry, which depreciatingly labels the users of psychoactive substances. Therewith, mediatic discourse often directs itself to concrete ends of sale, turning into a domination instrument, focusing in culture commercialization. However, in this study, the hypothesis pointed out is that the way media discourses are represented run through the bias of prejudice and stigmatization, leading drug users to a fragmented reality behind the walls of society. This is a bibliographical and documentary research, that consists of a qualitative evaluation, ranging from 2010 to July of 2016, of two great circulation newspapers in the state of Goiás - O Popular and Diário da Manhã -, aiming to identify signals that surpass the individuals / drug users. It is also worth to mention that this study uses the Critical Theory of the Society to substantiate a critical reflection on journalistic language associated to drug users and how this can influence its individual constitution and how they are seen by society and culture. In the first chapter, the history of drugs and the National Drug Policy was investigated; the second chapter presents a discussion of the fundamentals of cultural industry and how media perceives the individuals / drug users; data collected in the newspapers O popular and Diário da Manhã are discussed in the third chapter. As a conclusion, it is possible to highlight that society still understands and sees drug users with stigmatization and prejudice. In sum, this study pretends to reveal the benefits of a look beyond in the social imaginary, when related to the stigmatized drug users, in order to provide preventive actions and develop an ethical record with these individuals / drug users, without detracting or depreciating them.